Implementasi Metode Analytical Hierarchy Process Dan Interpolasi Linier Dalam Penentuan Lokasi Wisata Di Kabupaten Karangasem - Sudipa, I Gede Iwan; Wiguna, I Komang Arya Ganda; Putra, I Nyoman Tri Anindia; Hardiatama, Kadek (STIKOM Tunas Bangsa Pematangsiantar, 2021)
Bali is known for its tourism sector, so it has always been one of the alternative tourist destinations for local and foreign tourists. Almost every district in Bali has interesting tourist attractions to visit for tourists. When traveling, tourists usually decide to visit interesting tourist destinations. The number of tourist destinations available, often makes tourists confused about choosing a destination according to their preferences. Therefore, this research is intended for tourists to be able to determine alternative priority tourist sites in Karangasem Regency. In this study, data were collected from 75 respondents to find out alternative tourist sites in Karangasem, and to determine the criteria to be considered for traveling. These criteria are rides provided at tourist sites (C1), price of admission to tourist sites (C2), distance from tourist sites to city center (C3) and facilities provided at tourist sites (C4). 4 alternative tourism data used in the calculation by producing alternative tourist sites at Taman Ujung as the best alternative. The method used is the Analytical Hierarchy Process (AHP) to produce the weighted criteria, scoring the ticket price and distance values using Linear Interpolation and calculating the final value using the Cost and Benefit normalization process. The results of this study can provide alternative tourist locations for domestic tourists who want to vacation in Karangasem Regency.